Rare primary headaches in Italian tertiary Headache Centres: Three year nationwide retrospective data from the RegistRare Network. (July 2018) - Lupi, Chiara; Evangelista, Luana; Favoni, Valentina; Granato, Antonio; Negro, Andrea; Pellesi, Lanfranco; Ornello, Raffaele; Russo, Antonio; Cevoli, Sabina; Guerzoni, Simona; Benemei, Silvia
Background: Rare primary headaches are mainly included in Chapters 3, Trigeminal autonomic cephalalgias, and 4, Other primary headache disorders, Part One of the International Classification of Headache Disorders 3rd edition. Epidemiological data are scarce, mostly emerging from case series or small studies, with the exception of cluster headache. In order to overcome the knowledge gap about rare primary headaches, the RegistRare Network was launched in 2017 to promote research in the field. Methods: A retrospective cohort study including patients who, from April 30, 2014 to May 1, 2017, visited seven Italian tertiary Headache Centres, was undertaken to estimate in that clinical setting prevalence and incidence of headaches included in Chapters 3 and 4, Part One of the International Classification of Headache Disorders 3rd edition. Prevalent headache is defined as a headache recorded within the study timeframe, regardless of when the diagnosis was made. Incident headache is defined as a headache diagnosed for the first time in the patient during the study period. Results: Twenty thousand and eighty-three patients visited the participating centres, and 822 (4.1%) prevalent cases, of which 461 (2.3%) were incident cases, were registered. Headaches listed in Chapter 3 affected 668 patients, representing 81.3% of the total number of prevalent cases. Headaches listed in Chapter 4 affected 154 patients and represent 18.7% of the total number of prevalent cases. Cluster headaches represent the most frequently diagnosed rare headaches (70.4%). For 13 entities out of 20, no cases were registered in more than 50% (n ≥ 4) of the centres, and for 14 entities more than 50% of diagnoses were incident. Conclusions: This large, multicentre study gives the first wide-ranging snapshot of the burden in clinical practice of rare headaches and confirms that cooperative networks are necessary to study rare headaches, as their prevalence is often very low. The launch of a disease registry by the RegistRare Network will favour research in this neglected population of headache patients. Trial registration: NCT03416114.